Technological capacity of Local Productive Arrangements (APL'S): a prospective study in the municipalities of Pedras de Fogo (PB) and Itambé (PE) (Research, Society and Development, 2022)
The objective of this work was to carry out prospective research in order to identify potential Local Productive Arrangements (APLs) in the municipalities of Pedras de Fogo (PB) and Itambé (PE). The research was carried out in the period between August 1, 2019 and July 31, 2020, within the scope of the InovaPós project, through exploratory trips to the municipalities in question, where we sought to know the productive segments of the areas, focusing on the activities of greater potential for the formation of APLs, with a view to local development, through the generation of employment and income for the population and the engagement of local actors for the benefit of the region. For the purpose of carrying out the research, the qualitative, exploratory, bibliographic and documentary method and field research were used, with simple or unsystematic observation, non-participant, individual and carried out in real life, with the application of a non-structured interview, undirected and informal. The reality of these municipalities does not correspond to the potential found in the region. These municipalities have a business diversity that needs government and educational support and investments so that they can achieve the capacity to produce with operational excellence and expand their businesses beyond local consumption, adding quality and, consequently, value to the idealized product.